An investigation of the Tri-Bar gripping system on isometric muscular endurance - Drury, D. G.; Faggiono, H.; Stuempfle, K. J. (The Journal of Strength and Conditioning Research, 2004)
Recently, a new product called the Tri-Bar has been introduced as an alternative to the standard round weightlifting bar. The Tri-Bar has the same weight, length, and circumference as a standard weightlifting bar and differs only in that the shape of the bar is formed like a triangle with rounded edges. Theoretically, the shape of the bar will enhance gripping comfort and increase muscular endurance. We studied 32 moderately trained males who were free from upper-body injury or limitation. Each participant completed 4 visits to the lab as part of 2 separate investigations. The first investigation was a comparison of straight-arm hang times while grasping a standard Olympic bar or a Tri-Bar attached to the top of a power rack. The second investigation involved grasping a standard revolving cable handle or a Tri-Bar revolving handle attached to a weight equal to half the subject's body weight. In both investigations, time was used as a measure of isometric muscular endurance. Differences were determined using a dependent t-test, and a level of significance was set at p < 0.05. Results and conclusion: Mean hang times were significantly longer when the men hung from the Tri-Bar (107.6 seconds) versus the standard bar (95.4 seconds) (p = 0.015). Conversely, in the investigation using the revolving handles, the round bar produced longer grasping times (71.5 seconds) than the Tri-Bar (62.6 seconds) (p = 0.000). The results of this investigation indicate that a fixed and stable Tri-Bar may help to increase hang time, but a Tri-Bar free to rotate within the grasp may decrease grasping time in comparison to a standard round handle. With regard to exercises that require isometric grasping, the Tri-Bar may be an effective alternative to the standard bar for increasing isometric grasping endurance.